CONSTITUTIONAL OBLIGATIONS OF INDONESIAN GOVERNMENT DURING COVID-19 PANDEMIC: A CRITICAL APPRAISAL - Refisyanti, Sonya Whisler (Indonesian Comparative Law Review, 2021)
The research aims to evaluate the Indonesian government’s constitutional obligations and responses to protect citizens from coronavirus. The research is normative legal research using a statute, case, and comparative approach. The research findings reveal that first, the 1945 Constitution and Indonesian Human Rights Act state that the government has a responsibility to protect citizens’ human rights. Also, Health Quarantine Act, Health Act, Disaster Management Act, and Outbreaks of Infectious Diseases Act mention that the government has responsibility for any health efforts carried out during the Covid-19 Pandemic. Second, the government’s policies, such as arranging the Covid-19 Task Force and performing Large-Scale Social Restrictions, were late, and lack of coordination between central and local governments. Third, the government’s obstacles in handling the Covid-19 Pandemic are the policy not implemented effectively and adequately, ignorance and slow responses from the beginning, and low level of community awareness and individual discipline. The research recommends that, in the future, the government shall immediately take some prevention efforts and implement a strict lockdown policy for regions that have reached a particular infection level. The community also has to build their awareness and discipline to help the government deal with the COVID-19. Therefore, the spread of COVID-19 can be appropriately anticipated and controlled.